Committing to results : improving the effectiveness of HIV/AIDS assistance : an OED evaluation of the World Bank's assistance for HIV/AIDS control - Ainsworth, Martha, 1955- (World Bank operations evaluation study., 2005)
This evaluation assesses the development effectiveness of the World Bank's country-level HIV/AIDS assistance defined as policy dialogue, analytic work, and lending with the explicit objective of reducing the scope or impact of the AIDS epidemic. The evaluation identifies findings from this experience and makes recommendations to improve the relevance, efficiency and efficacy of ongoing and future activities. This is the first comprehensive evaluation of the World Bank's HIV/AIDS support to countries, from the beginning of the epidemic through mid-2004. Because the Bank's assistance is for impl.